If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x+4-2x=(x=8)
We move all terms to the left:
5x+4-2x-((x)=0
We add all the numbers together, and all the variables
3x-(x+4=0
| 10v-91=3v-14 | | -8=1+3m | | 5=-5+5u | | 0=80+(9x+4)+(16x-4) | | 64+-5x=24 | | j+19/5=7 | | 18=½(d+7) | | r+35=79 | | 7f-20=29 | | b/8-(-56)=68 | | 1x(3x+-9)=38 | | 91+-1x=87 | | s+28/10=-2 | | 6(t+4)=-1 | | u/7+42=44 | | p+21/9=4 | | 8(5x)=7x | | X2-y2=97 | | n+14/3=9 | | b/18=19 | | 3x+12+41+55=180 | | 90-3x=-30 | | g+18/3=7 | | 4x-44=5(4x+4) | | 2(3x+1)-3=-x-15 | | t/18=11 | | j-82/9=2 | | -4.8x2-1.6x+24=0 | | 2(2x+1)-5=-3x-31 | | 30-5r=8r-40 | | 2(t+18)=98 | | 3x+9=4(x+5) |